24.0k views
5 votes
How do you solve each system of equations?

1. 4x - 4y + 4z = - 4
4x + y - 2z = 5
-3x - 3y - 4z = -16

User Lastlink
by
5.8k points

1 Answer

4 votes

Answer:


x=1,y=3,z=1

Explanation:


4x-4y+4z=-4


4x=-4+4y-4z


x=-1+y-z

Substitute
x=-1+y-z into second equation:


4\left(-1+y-z\right)+y-2z=5


-4+4y-4z+y-2z=5


5y-6z-4=5


y=(6z+9)/(5)

Substitute
x=-1+y-z and
y=(6z+9)/(5) into the third equation:


(-41z-54)/(5)+3=-16


-41z-54=-95


z=1

Substitute
z=1 into
y=(6z+9)/(5):


y=3

Plug in y and z values into
x=-1+y-z:


x=1

User Gbixahue
by
5.9k points